BANTUAN HUKUM BAGI TERDAKWA TINDAK PIDANA DIBIDANG PERTAMBANGAN PADA TAHAP PENUNTUTAN - Himawan Setianto (Arena Hukum, 2013)
Abstract The purpose of the Legal Aid policy is a guarantee for the fulfillment of the rights of the poor to gain access to justice, both within and outside the judicial process; realizing the constitutional rights of citizens in accordance with the principle of equality before the law : ensuring sound implementation of legal aid implemented evenly across the region the Republic of Indonesia, and realize justice effective, efficient , and accountable . This paper aims to empirically analyze which led to the implementation of legal aid to the accused of criminal offenses in the field of mining on the stage of prosecution in the jurisdiction Katingan not run in accordance with the provisions of law (Criminal Procedure Code) as well as the legal implications for the defendant's criminal acts criminal offenses in the field of mining not accompanied by legal counsel at this stage of the prosecution. This paper uses socio-juridical approach (empirical research). The results of this study indicate that in jurisdictions Katingan was 100 % of respondents claimed not accompanied by legal counsel. In the absence of assistance by a lawyer or legal aid lawyers who assist the defendant in the prosecution stage, the effect on the defendant is that the defendant 's rights in obtaining legal aid does not exist or is not available, so it would be detrimental to the rights of the accused . Key words:legalaid, defendant, criminal offense, prosecutionÂ AbstrakTujuan penyusunan kebijakan Bantuan Hukum merupakan jaminan terpenuhinya hak bagi fakir miskin untuk mendapatkan akses keadilan, baik di dalam maupun di luar proses peradilan; mewujudkan hak konstitusional warga negara sesuai dengan prinsip persamaan di hadapan hukum: menjamin kepastian penyelenggaraan bantuan hukum dilaksanakan secara merata di seluruh wilayah Negara Republik Indonesia; dan mewujudkan peradilan yang efektif, efisien, dan dapat dipertanggungjawabkan.Tulisan ini bertujuan untuk menganalisis secara empiris yang menyebabkan pelaksanaan bantuan hukum bagi terdakwa tindak pidana dibidang pertambangan pada tahap penuntutan di wilayah hukum Kabupaten Katingan tidak berjalan sesuai dengan ketentuan perundang-undangan (KUHAP) serta implikasi hukum bagi terdakwa tindak pidana dibidang tindak pidana pertambangan yang tidak didampingi penasihat hukum pada tahap penuntutan. Tulisan ini menggunakan metode pendekatan yuridis sosiologis (penelitian empiris). Hasil penelitian ini menunjukkan bahwa di wilayah hukum Kabupaten Katingan ternyata 100% responden mengaku tidak didampingi penasehat hukum.Dengan tidak adanya pendampingan bantuan hukum oleh pengacara atau advokat yang mendampingi terdakwa dalam tahap penuntutan, pengaruhnya bagi terdakwa adalah bahwa hak-hak terdakwa dalam memperoleh bantuan hukum tidak ada atau tidak didapatkan, sehingga akan merugikan hak-hak terdakwa.Kata kunci:bantuan hukum, terdakwa, tindak pidana, penuntutan